Pengaruh Kombinasi Penambahan Sari Wortel (Daucus Carota, L) dan Tepung Hunkwee Pada Es Krim Kefir Terhadap Kualitas Fisik dan Kimia Es Krim Kefir (Faculty of Animal Science Universitas Brawijaya, 2015)
The purpose of this research was to determine the best combination of carrot juice (CJ) and hunkwee flour (HF) on manufacturing of kefir ice cream. The method of this research was experiment with Completely Randomized Design, 4 treatments and 4 replication, the treatments were without carrot juice + HF 5% (P0), CJ 1.5% + HF 3.5% (P1), CJ 3% + HF 2% (P2), CJ 4.5% + HF 0.5% (P3), the presentage based on Ice Cream Mix (ICM). The variables measured were antioxidant activity, viscosity, total solid and organoleptic (textur, taste and aroma). The data was analized by using Analysis Of Variance (ANOVA) continued by Honestly Significance Difference (HSD) test. The result of this research showed that the combination of carrot juice and hunkwee flour gave highly significant difference effect (P<0.01) on antioxidant activity, viscosity, total solid, texture and taste of kefir ice cream and did not give significantly difference effect (P>0.05) on aroma. Conclusion: the combination of carrot juice 1.5% + hunkwee flour 3.5% (P1) in kefir ice cream gave the best result.